Vibration isolation of buildings housed with sensitive equipment using open trenches – Case study and numerical simulations. Issue 115 (December 2018) - Sitharam, T.G.; Sebastian, Resmi; Fazil, Febin
Abstract: The vibration isolation of buildings housed with sensitive equipment is always a challenging one due to the stringent vibration criteria imposed on them. The paper presents a case study on the vibration isolation scheme adopted for an important building of space research agency. The vibration levels in the building had to follow the vibration criterion which is in the form of a set of one – third octave band velocity spectra, expressed as vibration criterion curves. Various sources that can generate vibrations in the building were identified and assessed. The external sources and the internal sources of vibration were analyzed and the possible limits of vibrations were evaluated. The selection procedure of design frequency, which is the significant step in the design of vibration isolation trench under the passive isolation scheme, is explained. Numerical simulations were developed to evaluate the influence of trench parameters on the amplitude reduction of Rayleigh waves propagating across the trench. Based on the results from numerical simulations, the vibration isolation trench was designed to reduce the amplitudes of vibrations produced from external and internal sources. Highlights: Vibration isolation for a building housed with sensitive equipment. Vibration criteria in terms of 1/3rd octave band velocity spectra. Analyses of external and internal sources of vibration. Determination of 1/3rd octave band frequencies. Numerical simulations for obtaining influence of trench dimensions in vibration reduction.